Association of energy intake and expenditure with obesity: A cross-sectional study of 150 pediatric patients following treatment for leukemia. (2nd January 2017) - Srivastava, Richa; Batra, Atul; Dhawan, Deepa; Bakhshi, Sameer
ABSTRACT: Increased obesity in leukemia survivors has been attributed to chemotherapy and radiation. Data on total energy intake (TEI) and total energy expenditure (TEE) are lacking in obese childhood leukemia patients after completion of therapy from India. We conducted a cross-sectional study in pediatric acute leukemia patients after completion of therapy wherein energy intake was assessed by 24-hour recall method. TEE was calculated using Harris–Benedict equation, by assessing the physical activity level using Physical Activity Questionnaire for children and basal metabolic rate by World Health Organization equation. Indian Academy of Pediatrics 2015 guidelines for BMI were used for defining overweight and obesity. Nutritional status was assessed in 150 leukemia patients after completion of therapy. Twenty-five percent of leukemia patients after completion of therapy were overweight and obese versus 11% of healthy controls ( p = 0.042). The mean ratio of TEI/required energy intake (REI), TEE/required energy expenditure (REE), and (TEI:REI)/(TEE:REE) were significantly higher in overweight and obese group versus nonobese survivors ( p < 0.001, p = 0.091, p < 0.001, respectively). Multivariate analysis showed higher income (HR-2.3, p = 0.04), increased TEI/REI (HR-4, p = 0.049) and higher (TEI:REI)/(TEE:REE) (HR-3.1, p = 0.039) to be significant factors predicting obesity. Obesity in leukemia patients after completion of therapy is associated with increased energy intake, causing imbalance between energy intake and TEE in these patients.